Dissection of mechanisms of Chinese medicinal formula Realgar-Indigo naturalis as an effective treatment for promyelocytic leukemia - Wang, Lan (National Academy of Sciences, 2008)
To enhance therapeutic efficacy and reduce adverse effects, practitioners of traditional Chinese medicine (TCM) prescribe a combination of plant species/minerals, called formulae, based on clinical experience. Nearly 100,000 formulae have been recorded, but the working mechanisms of most remain unknown. In trying to address the possible beneficial effects of formulae with current biomedical approaches, we use Realgar-Indigo naturalis formula (RIF), which has been proven to be very effective in treating human acute promyelocytic leukemia (APL) as a model. The main components of RIF are realgar, Indigo naturalis, and Salvia miltiorrhiza, with tetraarsenic tetrasulfide (A), indirubin (I), and tanshinone IIA (T) as major active ingredients, respectively. Here, we report that the ATI combination yields synergy in the treatment of a murine APL model in vivo and in the induction of APL cell differentiation in vitro. ATI causes intensified ubiquitination/degradation of promyelocytic leukemia (PML)-retinoic acid receptor α (RARα) oncoprotein, stronger reprogramming of myeloid differentiation regulators, and enhanced G(1)/G(0) arrest in APL cells through hitting multiple targets compared with the effects of mono- or biagents. Furthermore, ATI intensifies the expression of Aquaglyceroporin 9 and facilitates the transportation of A into APL cells, which in turn enhances A-mediated PML-RARα degradation and therapeutic efficacy. Our data also indicate A as the principal component of the formula, whereas T and I serve as adjuvant ingredients. We therefore suggest that dissecting the mode of action of clinically effective formulae at the molecular, cellular, and organism levels may be a good strategy in exploring the value of traditional medicine.